Lack of maintenance of motorway fences works against their intended purpose with potential negative impacts on protected species. - Farfán-Aguilar, Miguel Ángel; Fa, Julia E.; Martín-Taboada, Adrián; García-Carrasco, José María; Duarte, Jesús (Springer Nature, 2020)
Linear infrastructure intrusions into natural ecosystems, such as motorways and high-speed railways, causes direct loss of habitat but also impacts fauna through collisions. Wildlife road mortality is well documented and extensive conservation legislation exists in many countries to minimise the negative impact of these infrastructures. However, although these measures are implemented because of legislation, these structures are often not adequately maintained. Here we present data on the functionality of perimeter fences along two motorways in Malaga province (southern Spain) erected to prevent collisions with the common chameleon (Chamaeleo chamaeleon). We sampled the fences along the 14 km of the two motorways included in the 17 1 × 1 km squares of the study area. Our results show that the reptile fence is permeable throughout at those points where the metal sheeting was absent and where the vegetation had overgrown around the fence, hence allowing chameleons to cross. Given our results, we conclude that this situation is likely to be similar in other regions of Spain and in other countries. This is because construction/concessionary companies do not consider the environmental impact of construction projects in the medium and long term, and environmental authorities do not ensure that companies comply with the legislation.
Keywords: Autopistas - Impacto ambiental; Especies protegidas; Camaleones - Efectos de la modificación del hábitat; Camaleones - Protección; Chamaeleo chamaeleon; Human-wildlife conflict; Anthropised areas; Conservation